How to directly measure a Kondo cloud's length - Park, Jinhong; Lee, S-S B; Oreg, Yuval; Sim, H-S (Physical review letters, 2013)
We propose a method to directly measure, by electrical means, the Kondo screening cloud formed by an Anderson impurity coupled to semi-infinite quantum wires, on which an electrostatic gate voltage is applied at distance L from the impurity. We show that the Kondo cloud, and hence the Kondo temperature and the electron conductance through the impurity, are affected by the gate voltage, as L decreases below the Kondo cloud length. Based on this behavior, the cloud length can be experimentally identified by changing L with a keyboard type of gate voltage or tuning the coupling strength between the impurity and the wires.